Basic researchMyeloma cells inhibit osteogenic differentiation of mesenchymal stem cells and kill osteoblasts via TRAIL-induced apoptosis - Fu, Jinxiang; Wang, Panjun; Zhang, Xiaohui; Ju, Suguang; Li, Jie; Li, Binzhou; Yu, Sun; Zhang, Jianhua; Zhang, Xueguang (Archives of Medical Science, 2010)
Introduction : Myeloma bone disease (MBD) is the result of the increased activity of osteoclasts (OCs), which is not accompanied by a comparable increase of osteoblast (OB) function, thus leading to enhanced bone resorption. Osteoblasts can also regulate osteoclast activity through expression of cytokines, such as receptor activator of nuclear factor-kB ligand (RANKL), which activates osteoclast differentiation, and osteoprotegerin (OPG), which inhibits RANKL by acting as a decoy receptor. Material and methods : Based on a series of 21 patients with multiple myeloma (MM) and human osteoblast cell line HFOB1.19, we provide evidence that the bone marrow-derived mesenchymal stem cells (BMMSCs) of patients with MM exhibit normal phenotype, but showed reduced efficiency to differentiate into OBs as compared with normal controls. Results : In vitro assays showed that MM cells inhibited the potential of osteogenic differentiation of BMMSCs from healthy controls and rendered the OBs sensitive to TRAIL-induced apoptosis. There was no evidence of the formation of tartrate-resistant acid phosphatase positive OCs. The osteogenic differentiation of HFOB1.19 was also inhibited in the presence of RPMI 8266 or XG7 MM cells, as confirmed by von Kossa and ALP staining. Osteoblast s induced from BMMSCs supported survival and proliferation of MM cells, especially when the MM cells were cultured in medium containing rhTRAIL and dexamethasone. Multiple myeloma cells proliferated and grew well in the presence of residual OBs. Conclusions : Besides OCs, our results demonstrated that OBs and MM cells were dependent upon each other and made a microenvironment suitable for MM cells.